Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 3674104 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Aves", { "or" : [ "Country is Brazil", "Country is Argentina", "Country is Guyana", "Country is Uruguay", "Country is Chile", "Country is Paraguay", "Country is French Guiana", "Country is Suriname" ] } ] } The dataset includes 3674104 records from 275 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0050852-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences